Upaya Meningkatkan Motivasi Belajar Peserta Didik Pada Mata Pelajaran Matematika Melalui Pembelajaran Berdiferensiasi Berdasarkan Konten Di Kelas Xi TFLM-3 SMK Negeri 5 Surabaya - Nada Haristiani Barida; Fatkul Anam; Arif Santoso (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
In learning activities, motivation is an encouragement or process to direct students in achieving learning goals. The research was motivated by the very diverse problem of students' learning motivation in mathematics subjects in class XI TFLM-3 SMK Negeri 5 Surabaya. This can be seen from the results of the researcher's observations, where when they are about to start learning activities, many students still think that mathematics is less interesting and boring so that students are always less ready to start learning mathematics and the learning that was usually carried out by previous mathematics teachers was just learning. just lectures and assignments. This research aims to determine the increase in students' learning motivation in mathematics subjects through differentiated learning based on content. This research uses a type of Classroom Action Research (PTK) which consists of two cycles using data collection techniques in the form of questionnaires and observation. This questionnaire is used to determine learning satisfaction that motivates students after carrying out learning strategy treatment. The results of research using differentiated learning based on content show an increase in students' learning motivation from pre-cycle activities 63,8% to 73,1% in cycle I, then continued with cycle II. It shows that the presentation average of students' learning motivation in mathematics subjects is 83,2% From the results of this research it can be concluded that using differentiated learning based on content is successful in increasing students' learning motivation in mathematics subjects in class XI TFLM-3 SMK Negeri 5 Surabaya.